Analysis of Molecular Interactions of 8-Gingerol Compounds in Ginger (Zingiber officinale) as ACE Inhibitor - Yohanes Bare; Mansur s; Aprianus Pani Pili; Maria Helvina (BIOEDUSCIENCE, 2020)
Background: Hypertension is a disease with increasing characteristics of blood pressure. The ACE gene has a role in the conversion of ATI to ATII in hypertensive conditions. Healing is done by using the 8-gingerol content contained in ginger. The purpose of this study is to analyze the molecular interaction that occurs between 8-gingerol and ACE. Method: ACE model proteins (ID: 3bkk) were obtained from the Bank Data Protein database (PDB) through 8-gingerol ligands (CID: 168114) obtained from the PubChem database. ACE and 8-gingerol were docked by Discovery Study Client 4.1 software. Analysis of amino acid residues, binding energy, Van der Waals forces, and hydrogen bonds formed using Discovery Studio Client 4.1. Results: The interaction between 8-gingerol and ACE showed that there were seven amino acid residues that interacted with 8-gingerol, also found hydrogen bonds, hydrophobic and Van der Waals forces that strengthen and stabilize these bonds. Conclusion: the interaction of 8-ginger with the active side of ACE is determined as an ACE inhibitor, the inhibition is a significant effect on the obstruction of ACE conversion.